Impact of preoperative surgical anxiety on postoperative surgical recovery among surgical patients: role of surgical coping - Asma Rashid; Muhammad Naveed Riaz (Journal of the Pakistan Medical Association, 2021)
Objective: The present study examined the moderating impact of surgical coping in the relationship between pre-operative surgical anxiety and post-operative surgical recovery in surgical patients. Methods: The study was carried out in surgical departments of various hospitals situated in different areas of Province of the Punjab including Allied Hospital Faisalabad, DHQ Teaching Hospital Sargodha, Jinnah Hospital Lahore and Margalla Institute of Health Sciences Rawalpindi over the period of one-year May 1, 2018 to May 1, 2019. It was a descriptive research based on survey research design A purposive sample of pre-operative and post-operative surgical patients (N = 200) from Amsterdam Pre-operative Anxiety and Information Scale1, Surgical Recovery Scale2, and Coping with Surgical Stress Scale3 were used to collect information on study variables. Moderation analysis applied through PROCESS Marco 3.2. Results: Findings revealed that only two coping strategies including threat avoidance (p<.001) and information seeking (p<.001) moderated the relationship between surgical anxiety and surgical recovery of surgical patients. Conclusion: The study shed light on the importance of educating surgical patients regarding the use of appropriate coping strategies for their prompt recovery from surgery. The study has applied significance in the field of health psychology in general and for surgical patients in particular. Keywords: Surgical anxiety, surgical recovery, coping, threat avoidance, information seeking. Continuous...